Meningkatkan Self Regulated Learning dengan Model Pembelajaran Siklis Sebagai Modal Dalam Menghadapi Era Society 5.0 - dyah luthfia Kirana (Indonesian Journal of Counseling and Development, 2022)
Self-regulated learning is the ability of individuals to generate learning activities on their initiative that can influence their thoughts, feelings, strategies, and behaviour to achieve a goal in the learning process. Self-regulated learning is a capability that can be an asset in the success of the independent learning curriculum and in facing the era of society 5.0, which is centred on technology. In the era of society 5.0, the learning process can occur anywhere and anytime. Therefore, educators must be able to provide effective learning methods that can increase learner self-regulation. This study uses literature studies to examine learning methods that can enhance self-regulated learning. The study results show that the cyclical method is a learning method based on cycles of self-regulated learning that can be used to improve students' self-regulated learning by applying four stages to the learning process, namely, the stages of planning, monitoring, evaluation, and reflection